The State of Healthcare Facilities to Provide Diabetes, Cardiovascular and Chronic Respiratory Disease Related Services in Bangladesh (Dhaka University Journal of Science, 2022)
The rapid rise of diabetes, cardiovascular disease (CVD) and chronic respiratory disease (CRD) are causing serious challenges forBangladesh to achieve the sustainable development goal (SDG) target 3.4 by 2030. The study aims to describe the state of healthcarefacilities to provide diagnosis and treatment for diabetes, CVD and CRD related services in Bangladesh. This cross-sectional studyused data from 2017 Bangladesh Health Facility Survey (BHFS). A total of 406 health facilities providing all three services wereconsidered for this study. Findings of the study illustrated that there were rural-urban disparities in healthcare facilities to providediabetics, CVD, CRD related services. Diabetics and CRD related services were significantly higher in public healthcare facilitiesof urban areas compared to rural areas (P